Digital Readiness in The Digitalization of Public Service in Mekarsari Village, Selaawi Sub-District, Garut District - Eka, Anisya; Elisa Susanti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
This study examines the readiness of digital transformation in Mekarsari Village, Selaawi District, Bandung Regency. Although the village has started digitalizing services, there are still shortcomings in supporting infrastructure, human resource readiness, and funding availability. This study aims to further evaluate the readiness of service transformation and digitalization in Mekarsari village using the theory of digital readiness Musa (2010), which includes infrastructure, human resources, as well as government support and institutional management. The method used is qualitative by involving related actors in the digital transformation process. The results showed that: (1) there is a readiness of the availability of digitalization supporting infrastructure for services in Mekarsari Village. (2) human resources in Mekarsari Village are deployed as village bamboo craftsmen and self-taught in terms of digitization. (3) Analysis of government support in terms of funds and legal instruments is still lacking and only rely on funds and legal instruments provided by the central government. The conclusion of this study shows that in terms of public services and publications in Mekarsari Village are in the stage of transforming into a digital system. In accordance with the concept of Musa (2010), Mekarsari village has been trying to develop digitization in the village in accordance with the concept of readiness in the digitization of the village, but the readiness of the readiness must be continuously improved in order to create the maximum digitization of the village